Extensive reading and its impact on students' comprehension, vocabulary and reading attitude - Balakrishnan, Shamini A. (2013)
This current study investigates the impact of extensive reading on students’ comprehension, vocabulary and reading attitude. The study also explores the effectiveness of extensive reading and seeks to answer if extensive reading helps to promote positive attitude among students precisely in reading. The study is based on comprehensible input theory where students were engaged in large quantity of reading to achieve better comprehension and enhanced vocabulary together with positive attitude. The sample in this study consisted of 30 students of an intact class of Year 5. All of the students are of an average proficiency level. The extensive reading programme was administered for 12 sessions of 30 minutes each, outside the school timetable. Statistical and descriptive analysis were used for the findings purpose. Mean, standard deviation and the margin of improvement were calculated using the repeated measures T-test. The results of the data analysis indicated that extensive reading helped to improve the comprehension skill and vocabulary acquisition among the students. This was proven in terms of the marks obtained in the post-test after conducting the T-test using the SPSS. Extensive Reading has also helped to promote positive attitude toward reading which was seen through the descriptive analysis of attitude questionnaire and interview. Limitations, pedagogical implications and suggestions for future research are also indicated in this study.